Analysis of Voltage Drop and Illuminance Performance in 24 VDC LED Lightning System Using Different Driver Capacities - Muhammad Risqi Nuryana; Moh Hanif Assubhi (Universitas Pamulang, Prodi teknik Elektro, 2025)
This study examines how driver capacity influences voltage distribution and illuminance in a 24 VDC LED lighting installation. In many practical projects, differences in driver ratings are often assumed to have minimal impact as long as the load requirement is satisfied; however, voltage drop along the cable may affect the actual performance at the luminaire. An experimental measurement was conducted using identical LED fixtures connected through a 12-meter cable while varying the driver capacities at 20 W, 35 W, and 100 W. For each configuration, the output voltage from the driver, the voltage received at the LED terminals, and the resulting illuminance were recorded after stable operating conditions were reached. The observations show that higher driver capacity tends to provide slightly better voltage regulation at the load side, and this improvement is followed by an increase in measured illuminance. Although the voltage differences are relatively small, the trend consistently indicates the importance of proper driver selection in maintaining system effectiveness, especially in low-voltage installations with distribution distance. The results are expected to serve as a practical reference for electrical and lighting engineers in determining suitable driver specifications to achieve reliable and optimal lighting performance.